Boundary adaptive fault-tolerant control for a flexible Timoshenko arm with backlash-like hysteresis. (August 2021) - Zhao, Zhijia; Liu, Zhijie; He, Wei; Hong, Keum-Shik; Li, Han-Xiong
Abstract: This study is concerned with a novel adaptive fault-tolerant control design for a flexible Timoshenko arm considering the effects of actuator failures, backlash-like hysteresis, and external disturbances. First, the actuator failures and backlash-like hysteresis are integrated together and resolved into desired control signals and nonlinear errors. Second, these errors and external disturbances are deemed as composite disturbance terms to be handled with adaptive techniques. Third, adaptive fault-tolerant controllers with online updates are established to eliminate the shear deformation and elastic oscillation, lay the arm in a desired angle, counteract the hybrid effects of actuator failures and hysteresis, and deal with the uncertainty of composite disturbances. Then, based on the Lyapunov's stability theory, the proposed strategy guarantees the uniformly bounded stability in the controlled system. Finally, numerical examples are presented to illustrate the efficacy of the suggested scheme.